Perceptions of first professional year medical undergraduates and biochemistry faculty on one minute paper: A feedback tool to interactive lectures - Smita Sonoli; Atteequeurrehman Harlapur; Vanishree Bubanale; Reshma Channashetti; Sangamma Sajjan; Sagar Nitturkar (Journal of Krishna Institute of Medical Sciences University)
Background: The shift to Competency-Based Medical Education (CBME) requires student-centered teaching methods. The One-Minute Paper (OMP) is a quick feedback tool designed to assess and address students understanding of lecture content, promoting active learning and reflective thinking. Aim and Objectives: To evaluate the effectiveness and perceptions of the OMP as a feedback mechanism among first-year MBBS students and biochemistry faculty. Material and Methods: This cross-sectional study was conducted over two consecutive academic years (2021-2023) at KAHER's JNMC, Belagavi. The study included 400 MBBS students and 11 biochemistry faculty members. A Quick Response Code (QRC)-enabled OMP system was implemented after interactive lectures. Feedback was collected and analyzed using descriptive statistics. Results: The study covered 148 interactive lectures, with 170 ± 15 OMP responses per lecture. Among students, 73% found the OMP helpful for voicing doubts, 86% noted that least-understood concepts were addressed, and 60% felt confident in applying learned concepts. Faculty reported the OMP as a valuable formative and self-assessment tool, with 100% acknowledging its role in improving lecture quality and curriculum refinement. Conclusions: OMP is a simple and efficient tool for fostering active learning, addressing knowledge gaps, and improving teaching quality. It aligns well with CBME principles and has the potential for wider adoption across medical education curricula.